“Smooth Muscle Cell Stiffness Syndrome”—Revisiting the Structural Basis of Arterial Stiffness - Sehgel, Nancy L.; Vatner, Stephen F.; Meininger, Gerald A. (Frontiers in Physiology, 2015)
In recent decades, the pervasiveness of increased arterial stiffness in patients with cardiovascular disease has become increasingly apparent. Though this phenomenon has been well documented in humans and animal models of disease for well over a century, there has been surprisingly limited development in a deeper mechanistic understanding of arterial stiffness. Much of the historical literature has focused on changes in extracellular matrix proteins – collagen and elastin. However, extracellular matrix changes alone appear insufficient to consistently account for observed changes in vascular stiffness, which we observed in our studies of aortic stiffness in aging monkeys. This led us to examine novel mechanisms operating at the level of the vascular smooth muscle cell (VSMC) – that include increased cell stiffness and adhesion to extracellular matrix – which that may be interrelated with other mechanisms contributing to arterial stiffness. We introduce these observations as a new concept – the Smooth Muscle Cell Stiffness Syndrome (SMCSS) – within the field of arterial stiffness and posit that stiffening of vascular cells impairs vascular function and may contribute stiffening to the vasculature with aging and cardiovascular disease. Importantly, this review article revisits the structural basis of arterial stiffness in light of these novel findings. Such classification of SMCSS and its contextualization into our current understanding of vascular mechanics may be useful in the development of strategic therapeutics to directly target arterial stiffness.